Cost-benefit analysis of spillover tax revenues of high-speed rail in Taipei, China - Naoyuki Yoshino; Kai Xu; Deepanshu Agarwal; Kallidaikurichi Seetharam (Asian Development Bank Institute (ADBI), 2023)
This paper introduces the concept of spillover tax revenues, which are also known as "indirect" or "secondary revenues," or "externality effects." Based on a case study of high-speed rail in Taipei,China, the spillover tax revenues are identified using the regional tax data through a DID analysis. This paper proposes alternatives for financing infrastructure investments with incorporation of the floating bond and land trust scheme. Further on, a cost-benefit analysis is carried out for the case from both the public and private sector's perspective. Compared to the traditional investment scheme, the proposed financing schemes show a significant improvement of the IRR. The introduction of spillover tax revenues is essential to meet the needs of infrastructure investment in Asia. Increased spillover tax revenues should be shared with the local government and private investors. Combined with the innovative financing schemes, the improved IRR would induce private-sector financing in infrastructure investments.
Keywords: R40; R52; 330; spillover tax revenues; floating bond; land trust scheme; private investment; high-speed rail